2012
DOI: 10.1093/cid/cis551
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Diarrhea: Evaluation and Treatment of Causes Other Than Clostridium difficile

Abstract: Diarrhea is common among hospitalized patients but the causes are distinct from those of diarrhea in the community. We review existing data about the epidemiology of nosocomial diarrhea and summarize recent progress in understanding the mechanisms of diarrhea. Clinicians should recognize that most cases of nosocomial diarrhea have a noninfectious etiology, including medications, underlying illness, and enteral feeding. Apart from Clostridium difficile, the frequency of infectious causes such as norovirus and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
95
0
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(105 citation statements)
references
References 52 publications
2
95
0
8
Order By: Relevance
“…Valenstein et al reported the findings of a College of American Pathologist Q-Probe, which demonstrated that when interventions are not in place, almost 40% of stool cultures may be submitted after the third day of hospitalization, with a yield of only 0.6% (10). It is also well known that diarrhea that develops after hospitalization is more likely to be associated with Clostridium difficile, medications, enteral feedings, or the underlying illness (11,12). Exceptions to the "3-day rule," however, have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Valenstein et al reported the findings of a College of American Pathologist Q-Probe, which demonstrated that when interventions are not in place, almost 40% of stool cultures may be submitted after the third day of hospitalization, with a yield of only 0.6% (10). It is also well known that diarrhea that develops after hospitalization is more likely to be associated with Clostridium difficile, medications, enteral feedings, or the underlying illness (11,12). Exceptions to the "3-day rule," however, have been described.…”
Section: Discussionmentioning
confidence: 99%
“…1 Despite efforts on infection control and prudent antibiotic stewardship, the incidence of Clostridium difficile infection (CDI)…”
Section: Introductionmentioning
confidence: 99%
“…Besides the potential to induce colitis under certain circumstances, enteric carriage of K. oxytoca may be important for the transmission of antibiotic resistance genes to other bacteria and as a source of nosocomial infections (7,8). Indeed, this bacterium and the closely related species Klebsiella pneumoniae are important human pathogens causing hepatobiliary infections and infections of the urinary tract and soft tissue, in addition to nosocomial pneumonia (9)(10)(11). In recent years, multidrug-resistant strains of both species have emerged as an important problem in the health care system (7,12).…”
mentioning
confidence: 99%